VIROLOGICAL AND SEROLOGICAL DIAGNOSIS OF RABIES IN BATS FROM AN URBAN AREA IN THE BRAZILIAN AMAZON - OLIVEIRA, Rubens Souza de; COSTA, Lanna Jamile Corrêa da; ANDRADE, Fernanda Atanaena Gonçalves de; UIEDA, Wilson; MARTORELLI, Luzia Fátima Alves; KATAOKA, Ana Paula de Arruda Geraldes; ROSA, Elizabeth Salbé Travassos da; VASCONCELOS, Pedro Fernando da Costa; PEREIRA, Armando de Souza; CARMO, Antônio Ismael Barros do; FERNANDES, Marcus Emanuel Barroncas (Revista do Instituto de Medicina Tropical de São Paulo, 2015)
The outbreaks of rabies in humans transmitted by Desmodus rotundus in 2004 and 2005, in the northeast of the Brazilian State of Para, eastern Amazon basin, made this a priority area for studies on this zoonosis. Given this, the present study provides data on this phenomenon in an urban context, in order to assess the possible circulation of the classic rabies virus (RABV) among bat species in Capanema, a town in the Amazon basin. Bats were collected, in 2011, with mist nets during the wet and dry seasons. Samples of brain tissue and blood were collected for virological and serological survey, respectively. None of the 153 brain tissue samples analyzed tested positive for RABV infection, but 50.34% (95% CI: 45.67-55.01%) of the serum samples analyzed were seropositive. Artibeus planirostris was the most common species, with a high percentage of seropositive individuals (52.46%, 95% CI: 52.31 52.60%). Statistically, equal proportions of seropositive results were obtained in the rainy and dry seasons (c2 = 0.057, d.f. = 1, p = 0.88). Significantly higher proportions of males (55.96%, 95% CI: 48.96-62.96%) and adults (52.37%, 95% CI: 47.35-57.39%) were seropositive. While none of the brain tissue samples tested positive for infection, the high proportion of seropositive specimens indicates that RABV may be widespread in this urban area.